ENFOQUE SISTÉMICO DE INVESTIGACiÓN Y DESARROLLO PARA LA MEJORA CONTINUA DE LA EDUCACIÓN (Journal on studies and research of academic knowledge, 2008)
This work is developed from a project of investigation that it tries to analyze, to describe and to sustain, with scientific criterion, the underlying implications to an effective and harmonic symbiosis between the National University of Itapúa (UNI), through the Faculty of Humanities, Social Sciences and Guaraní Culture and the system of average education in relation to the educative management and the necessities of investigation and development (I+D) in a frame of continuous improvement of the one of the average education in the Region.With the exposed thing it is tried to maintain the Social hypothesis that the conceived educative investigation under a systemic model of development for a strategic management of the continuous improvement of the quality of the education is feasible from the conditions of the context of Pedagogical Zone of 2 Itapúa and the participation of the Faculty of Humanities, Sciences and Guaraní Culture of the National University of Itapúa.The base paradigm with which east work is identified is qualitative or the interpretative one, looking for to include/understand and to interpret the reality from the optics of the own actorsinvolved in the investigated phenomenon.The proposals could have practical sustenance in a strategic plan based on a systemic model of the investigation and development that allows establishing rules and networks of inter institutional relations, directionalities and intentionalities shared within the educative system of the region. The development of the plan would leave from the conception of an integrated system of investigation and development (SI+D) for the management of the continuous improvement of the educative quality caused by investigation equipment and management integrated by educative agents of the Faculty of Humanities, Social Sciences and Guaraní Culture and those of the Primary Education and Measured Public, on the basis of the conditions of the regional educative context.
Keywords: System; strategic educative management; investigation and development; educative quality